Flickering nanometre-scale disorder in a crystal lattice tracked by plasmonic flare light emission - Cloudy Carnegie (Nature Portfolio, 2020)
Dynamic restructuring of metal nanoparticle surfaces greatly influences their catalytic, electronic transport, and chemical binding functionalities. Here, the authors show that non-equilibrium atomic-scale lattice defects can be detected in nanoparticles by using nano-optics at the sub-5nm scale.